The introduction of Fair Trade in Poland: Opportunities and challenges - Kinga Boenning (Banwa, 2009)
Fair Trade aims to improve the working and living conditions of producers by paying a higher price for their products as well as off ering additional support. Th e strategic goals of Fair Trade are to support marginalized producers and workers to attain economic security and to make a decent living from their farming activities. In Poland, Fair Trade is expanding very rapidly. Given this development, an ongoing market for Fair Trade products can safely be assumed, but greater coordination among actors and common activities between NGOs and interested businesses may accelerate development even further.
Keywords: 330; Central and Eastern Europe; civil society; consumption; Fair Trade; Poland; smallholder producers